Application of Article 7 of the Rome II Regulation in the case of Begum v. Maran - Wydmański, Wojciech (CUADERNOS DE DERECHO TRANSNACIONAL, 2025)
The subject of this article is an analysis of the English court’s consideration of the applicable law in Begum v. Maran. It concerned a claim against a multinational corporation for compensation for the death of a shipyard worker in Bangladesh. The court in that case addressed the appropriateness of using Article 7 of the Rome II Regulation, a special conflict of laws rule that determines the law applicable to environmental damage. The purpose of the paper is to show that the construction adopted in Article 7 Rome II is favourable to persons injured by environmental pollution, however, the scope and interpretation of this provision is narrowly applied. The paper will present the position of litigants and the court, as well as the views presented in other decisions of English and EU courts and representatives of the doctrine of private international law.